2016
DOI: 10.1093/ejcts/ezw099
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after surgical treatment of chronic thromboembolic pulmonary hypertension: dealing with different patient subsets. A single-centre experience

Abstract: Despite the increased perioperative risk and mortality, PEA should not be denied to patients with extremely elevated PVR but clear indication for surgery. Keeping increased perioperative risk and mortality in mind, significant pressure reduction and improved functional outcome can be achieved in the majority of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Our study, conducted in a large cohort of consecutive patients with CTEPH, confirms the results of the international CTEPH Registry that PEA is an independent predictor of survival [24]. In operated patients it was associated with an excellent long-term outcome with an estimated 5-year survival of 83%, similar to data from the international [24], Austrian [31, 32], Spanish [25], Italian [33] and Dutch CTEPH registries [34]. Although 482 patients (82%) had technically operable disease distribution, despite the proven benefits of PEA only 272 (49% of the total cohort) underwent surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Our study, conducted in a large cohort of consecutive patients with CTEPH, confirms the results of the international CTEPH Registry that PEA is an independent predictor of survival [24]. In operated patients it was associated with an excellent long-term outcome with an estimated 5-year survival of 83%, similar to data from the international [24], Austrian [31, 32], Spanish [25], Italian [33] and Dutch CTEPH registries [34]. Although 482 patients (82%) had technically operable disease distribution, despite the proven benefits of PEA only 272 (49% of the total cohort) underwent surgery.…”
Section: Discussionsupporting
confidence: 87%
“…[4][5][6] Predictors of in-hospital mortality in the German NIS Regarding predictors of mortality, the UK-PH registry demonstrated in 239 CTEPH patients that a preoperative pulmonary resistance above 1000 dyneÁsÁcm À5 was associated with increased perioperative mortality, whereas higher cardiac index and longer six-minute walk distance were associated with a better perioperative survival. 16 Similarly, an elevated PVR as well as NYHA class IV were identified as a predictor of 30-day mortality in 214 19 and 106 20 CTEPH patients who underwent PEA in previous studies. In the present study, NYHA class III/IV was also associated with increased in-hospital mortality in an univariate, but not in a multivariate logistic regression model.…”
Section: Comparison Of the German Nis With Other Study Cohorts Worldwidementioning
confidence: 73%
“…Data on the outcomes of lung transplantation in CTEPH can be extracted from only a few reported experiences and they are not satisfactory. Nierlick et al (3) reported that 3 of the 4 transplanted patients died shortly after the intervention due to multi-organs failure while the last patient had a good long-term outcome after transplantation. More recently, the systematic application of intraoperative cardio-circulatory support and its prolongation in the postoperative period have improved the surgical results of lung transplantation for PH even in case of CTEPH.…”
Section: Discussionmentioning
confidence: 99%